S46 Phagocytosis By Blood Neutrophils Is Not Attenuated In Patients With Chronic Obstructive Pulmonary Disease. (10th November 2014) - Walton, GM; Purvis, T; Chadwick, C; Stockley, RA; Sapey, E
Abstract : Rationale: All COPD phenotypes have airway neutrophilia but, despite this, bacteria associated infections are common, relate to decline and a significant proportion of patients have persistent airway colonisation. This is suggestive of innate immune dysfunction. In vitro studies have shown reduced neutrophil migratory accuracy in COPD (Sapey, Stockley et al . 2011) however, the ability of the neutrophil to contain bacterial infection upon arrival at a site of infection is poorly understood. Literature regarding the phagocytic ability of neutrophils from patients with COPD is conflicting and inconclusive. It is unclear whether responses change depending on the bacterial species present. We hypothesised that neutrophil phagocytosis during COPD is impaired, predisposing patients to increased inflammation and reduced bacterial clearance. Methods: Blood neutrophils were isolated from stable-state COPD patients and healthy age-matched controls (HC). Phagocytosis of both opsonised (with 10% pooled COPD serum) and unopsonised pHrodo™-conjugated Staphylococcus aureus bioparticles (SA, n = 20), or E scherichia coli bioparticles (EC, n = 10) and fluorescently labelled disease-relevant bacteria, Haemophilus influenzae (HI, n = 10) and Streptococcus pneumoniae (SP, n = 10) was assessed, at regular intervals over 60 min, using flow-cytometry. Results were confirmed using time-lapse video microscopy. Results: Peak phagocytosis was achieved at 60 min for unopsonised bacteria and 30 min for opsonised bacteria. There were no differences in time to peak phagocytosis between bacterial species. Blood neutrophils from patients with COPD and HC displayed similar phagocytic ability, in both percentage of neutrophils with phagocytic activity and the amount of SA, EC, HI or SP ingested (as indicated by MFI) (COPD vs. HC, p > 0.05 for all). This was ubiquitous to both opsonin independent and opsonin-dependant phagocytosis, and was consistent across all time points measured. A typical comparison is shown in figure one, with unopsonised SA data. Conclusions: Phagocytic ability of blood neutrophils from patients with COPD to ingest Staphylococcus aureus, Escherichia coli, Streptococcus pneumoniae and Haemophilus influenzae is not altered compared to age-matched healthy controls. This should be replicated in lung neutrophils to assess whether transmigration to the tissues affects function.